Sedimentary Responses to Climate Changes and Human Activities Over the Past 7400 Years in the Western Sunda Shelf - Wu, Kaikai; Shi, Xuefa; Lou, Zhanghua; Wu, Bin; Li, Jingrui; Zhang, Hui; Cao, Peng; Rahim Mohamed, Che Abd (Frontiers in Earth Science, 2021)
High-resolution records of grain size, major and trace elements, and Sr-Nd isotopes of Core K17 from the western Sunda Shelf were investigated to evaluate the response of weathering and terrigenous input to climatic changes and human activities over the past 7400 years. Sr-Nd isotopic results indicate that the Kelantan river is the main source of sedimentary material in the study core since the mid-Holocene. Chemical weathering levels are represented by the chemical index of alteration (CIA), αAlNa, and K2O/Al2O3 ratios; and geochemical and grain size proxies (including TiO2/CaO, Rb/Sr ratios, and grain size end-member) were used to establish variations of terrigenous input into the study core since 7400 cal yr BP. Based on these records, the evolution of weathering and terrigenous input processes in the western Sunda Shelf can be divided into four stages. During stage 1 (7400-3700 cal yr BP), increasing precipitation and decreasing temperature jointly balanced the relatively stable weathering and terrigenous sediment supply. Dramatically decreasing weathering rates were consistent with less rainfall and lower temperatures during stage 2 (3700-2600 cal yr BP). Heavy rainfall played a more important role than low temperature in controlling weathering and erosion, leading to increasing terrigenous input in stage 3 (2700-1600 cal yr BP). Because of the decoupling between weathering, erosion, and climate in the late Holocene (stage 4, since 1600 cal yr BP), increasing agriculture and related human activities likely dominated weathering and erosion relative to climate changes. Furthermore, the initial time at which human activity overwhelmed natural processes in the southern South China Sea is similar to that in the northern South China Sea. Our results highlight that human activities during the past 1600 years have gradually overwhelmed natural climatic controls on weathering and erosion processes in the western Sunda Shelf.